THE EFFECT OF DER, SALES AND INSTITUTIONAL OWNERSHIP ON THE VALUE OF MANUFACTURING COMPANIES IN THE AUTOMOTIVE SUB-SECTOR - Retno Suliati Suleiman; Rizka Maharani (GoAcademica Research dan Publishing, 2022)
The goal of this study was to determine the influence of DER, sales, and institutional ownership on the value of automobile manufacturing companies. This study employs a technique known as quantitative research. In this study, the dependent variable is the estimated company value using Price Book Value (PBV). Meanwhile, the independent variables in this study are the DER predicted using the Debt to Equity Ratio (DER), the Sales projected using the Ln (Total Assets), and the Institutional Ownership projected using the Institutional Ownership Ratio. Based on the results of data analysis, it can be concluded that: 1) The DER variable has a negative and insignificant effect on firm value; 2) Sales variable has a negative and insignificant effect on firm value; 3) Influential Institutional Ownership Variables A high level of institutional ownership will encourage the institutional investors to carry out greater supervisory efforts as well; 4) DER Sales and Institutional Ownership variables simultaneously have a significant effect on firm value.